2016
DOI: 10.17705/1jais.00426
|View full text |Cite
|
Sign up to set email alerts
|

Job Satisfaction in Agile Development Teams: Agile Development as Work Redesign

Abstract: Agile software-development advocates claim that an important value proposition of agile methods is that they make people more motivated and satisfied with their jobs. While several studies present anecdotal evidence that agile methods increase motivation and satisfaction, research has not theoretically explained or empirically examined how agile development practices relate to team members' feelings about their work. Drawing on the management and software-development literature, we articulate a model of job de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
180
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 146 publications
(189 citation statements)
references
References 70 publications
(111 reference statements)
6
180
0
3
Order By: Relevance
“…These approaches focus on the social nature of software development [16]. Values like commitment, openness and respect form the footing of all agile methods and lead to a higher perception of job satisfaction within software development teams [15]. Furthermore, additional factors like team awareness and team involvement foster cohesion within the team [16].…”
Section: Agile and Traditional Project Management Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These approaches focus on the social nature of software development [16]. Values like commitment, openness and respect form the footing of all agile methods and lead to a higher perception of job satisfaction within software development teams [15]. Furthermore, additional factors like team awareness and team involvement foster cohesion within the team [16].…”
Section: Agile and Traditional Project Management Methodsmentioning
confidence: 99%
“…Due to the differences in team composition and conducting tasks, different types of subgroups form in agile and traditional IT projects, based on faultlines, which are dividing lines that are based on attributes of diversity of team members [7,14]. For instance, agile methods emphasize values like commitment, openness and respect [15]. This creates a different form of exchange between the team members [16], which in turn influences the formation of subgroups.…”
Section: Introductionmentioning
confidence: 99%
“…In many cases, these papers do not measure the level of use of agile methods or practices, but rather, just the high level concept of use of that method. However, more recent research has shown that the impact of these agile practices (such as using pair programming) may take both direct and indirect paths to a dependent variable (such as code quality) [36]. Furthermore, the measurement of agile practices as opposed to the use of a "methodology" has Page 5466 become more common [e.g., 25,36].…”
Section: Measurementmentioning
confidence: 99%
“…However, more recent research has shown that the impact of these agile practices (such as using pair programming) may take both direct and indirect paths to a dependent variable (such as code quality) [36]. Furthermore, the measurement of agile practices as opposed to the use of a "methodology" has Page 5466 become more common [e.g., 25,36]. This change of focus from method to practice is appropriate; as research shows that few teams adopt agile methodologies as a whole, but rather tailor them to their individual situations [11].…”
Section: Measurementmentioning
confidence: 99%
See 1 more Smart Citation